LAWS OF SYNERGY IN THE ECONOMY, BUSINESS AND THE OPERATION PROCESS OF THE MANUFACTURE (ORGANIZATION) - Yakimtsov, Viktor (European Scientific Journal, ESJ, 2015)
This article is devoted to issues of application of laws, synergy machinery in the economy, business and operation process of the manufacture (organization). There are presented concepts, classification of synergy effects and grounds of merger of the organizations. There are presented some fundamental principles, on which the strategic planning of the development of entrepreneurial activity (business) shall be based. There is determined a necessity of application of synergy laws and synergy effect throughout the economy.